A Simple and Rapid LC-MS/MS Method for Quantification of Total Daidzein, Genistein, and Equol in Human Urine - Shikha Saha; Paul A Kroon (Journal of Analytical Methods in Chemistry)
Isoflavones and isoflavandiols have shown many health benefits, such as reducing cardiovascular disease, cancer, age-related disease, and osteoporosis. However, to investigate the relationships between consumption of isoflavones and their health benefits, it is important to be able to accurately quantify exposure in the large numbers of samples typically produced in association studies (i.e., several thousands). Current methods rely on solid-phase extraction protocols for sample cleanup, resulting in protracted extraction and analysis times. Here, we describe a fast and easy sample preparation method of human urine samples for subsequent quantification of daidzein, genistein (isoflavones), and equol (isoflavandiol) using LC-MS/MS. Sample preparation involves only the addition of dimethylformamide (DMF) and formic acid (FA) after enzymatic hydrolysis of their metabolites by a β-glucuronidase and sulfatase mixture. The method was validated by precision, linearity, accuracy, recoveries, limit of detection (LOD), and limit of quantification (LOQ). Linear calibration curves have been shown by daidzein, genistein, and equol. The correlation coefficients values are r2 > 0.99 for daidzein, genistein, and equol. LOD for daidzein and genistein was 1 ng/ml and equol was 2 ng/ml. Recoveries were >90%, and the relative standard deviation for intraday (<10%) and interday (≤20% over 10 days) was good. This method is suitable for quantification of isoflavones and the microbial metabolite equol in human urine and is particularly useful where large numbers of samples require analysis.